Assessment of Central Arterial Hemodynamics in Children: Comparison of Noninvasive and Invasive Measurements. (9th September 2020) - Cai, Tommy Y; Haghighi, Marjan M; Roberts, Philip A; Mervis, Jonathan; Qasem, Ahmad; Butlin, Mark; Celermajer, David S; Avolio, Alberto; Skilton, Michael R; Ayer, Julian G
Abstract: Background: In adults, central systolic blood pressure (cSBP) and augmentation index (cAIx) are independently associated with cardiovascular events and mortality. There is increasing interest in central hemodynamic indices in children. We aimed to assess the accuracy of current techniques against invasive intra-aortic measurements in children. Methods: Intra-aortic pressure waveforms were recorded with simultaneous brachial, radial, and carotid waveforms in 29 children (6.7 ± 3.9 years old) undergoing cardiac catheterization. Adult and age-appropriate transfer functions (TFs) (brachial adult: b-aTF; radial adult: r-aTF; radial for 8-year-old children: TF8; and radial for 14-year-old children: TF14) were used to synthesize central aortic waveforms from peripheral waveforms calibrated either to invasively or noninvasively recorded BP. Central hemodynamic indices were measured by pulse wave analysis. Results: cSBP measured from invasively calibrated r-aTF (β = 0.84; intraclass correlation coefficient = 0.91; mean error ± SDD = −1.0 ± 5.0 mm Hg), TF8 (β = 0.78; intraclass correlation coefficient = 0.84; mean error ± SDD = 4.4 ± 5.6 mm Hg), and TF14 (β = 0.82; intraclass correlation coefficient = 0.90; mean error ± SDD = 2.0 ± 4.7 mm Hg)-synthesized central waveforms correlated with and accurately estimated intra-aortic cSBP measurements, while noninvasively calibrated waveforms did not. cAIx derived from TF-synthesized central waveforms did not correlate with intra-aortic cAIx values, and degree of error was TF-dependent. Conclusions: The currently available r-aTF accurately estimates cSBP with invasive pulse pressure calibration, while age-appropriate TFs do not appear to provide additional benefit. Accuracy of cAIx estimation appears to be TF dependent.